Simultaneous enrichment of Cd, Pb, Ni, and Al and their determination in water by STAT-FAAS - Yaman, M (Marcel Dekker Inc, 2001)
Toxic metals such as Cd, Pb, Ni and Al were determined in drinking, dam lake, stream and lake water by using flame atomic absorption spectrometry (FAAS) after enrichment. In the enrichment procedure, their chelates with cupferron were preconcentrated on activated carbon. For increasing the sensitivity of cadmium and lead, slotted tube atom trap (STAT) was used as accessory in the FAAS. 150 fold preconcentration was achieved.
Keywords: cadmium; lead; nickel; aluminium; water; AAS; enrichment